Os efeitos da confiança institucional na relação entre crença no mundo justo e vitimização secundária de pessoas presas injustamente - Leal, Tatiana Cavalcanti de Albuquerque (2022)
Miscarriages of justice, like wrongful convictions, are severe flaws in the justice system that happen daily in all justice systems in the world. The majority of these cases are due to institutional misconduct. Society, however, blames, derogates, and does not offer support to wrongfully convicted persons, resulting in their secondary victimization. We address this phenomenon by proposing the hypothesis that the Belief in a Just World (BJW) predicts the secondary victimization of wrongfully convicted people and that the level of trust in institutions mediates this relationship. We developed a research program of three articles comprising five studies. The first article consisted of a preliminary study (N = 381) in which we assessed the level of trust in several institutions, and we compared these levels between two different political contexts in Brazil, the years 2018 and 2019. We found a low level of institutional trust, specifically in democratic political institutions. We also found a change in these levels from one context to another, as trust in coercive institutions was stronger in 2019 than in 2018. In the second article (N = 381), also a preliminary study, we investigated whether the institutional trust was related to the BJW and if this relationship was moderated by social and political factors. The analysis revealed that the BJW related to institutional trust indeed, but only in leftwing and lower-income participants. The third article, with three studies, focused more directly on the nuclear hypothesis of this thesis. We experimentally tested our main hypothesis: that the BJW would predict the secondary victimization of wrongfully convicted people and that it would happen indirectly through institutional trust, depending on whether injustice threatened the BJW. In the first study (N = 150), we experimentally activated the threat to the BJW. We found that trusting social coercive, political, and justice institutions mediated the relationship between BJW and blaming the wrongfully convicted victim. Moreover, trusting political and justice institutions also mediated this relationship when it came to minimizing the victim's suffering. In the second study (N = 539), we replicated the first study with a larger sample. Specifically, in the threat condition to the BJW, we verified that trusting the media mediated the relationship between the BJW and victim blaming. Likewise, trusting social coercive and justice institutions mediated the relationship between this belief and minimizing the victim's suffering and trusting social coercive institutions mediated this relationship with the dimension of victim avoidance. The third study (N=252) was conducted in England, a cultural context where democracy is well consolidated. We found that trust in political institutions mediated the relationship between BJW and victim blaming and minimizing the victim's suffering. We confirmed the role of mitigation of the secondary victimization played by trust in justice institutions. In general, the results have been consistent with the hypothesis proposed and showed how the BJW contributes to the process of legitimation of injustices committed by nuclear institutions of the Brazilian and English society. It also points out that trusting these institutions can sometimes be a bridge for this legitimation.